Formation of emulsion properties with celery root powder - Niemirich, Oleksandra; Ustymenko, Ihor; Havrysh, Andrey; Mamchenko, Liudmyla; Skyrda, Olena; Zhytnetskyi, Ihor; Podobiy, Olena; Hubenia, Vyacheslav; Lulka, Alexander; Tkachuk, Yuriy; Pushka, Olga; Doroshkevych, Ruslan (My University, 2023)
Celery root powder obtained by drying with mixed heat supply, which is a promising raw material of plant origin as a source of biologically active substances for use in the composition of culinary products of polyphasic type due to functional and technological properties contributes to the formation of appropriate emulsion properties, prescription ingredients of this plant material. The work aims to study the effect of celery root powder obtained by drying with mixed heat supply on sedimentation resistance, structure and rheological properties of emulsions for a wide range of culinary products.
Keywords: кафедра готельно-ресторанної справи; кафедра технології ресторанної і аюрведичної продукції; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; celery root powder; microstructure; sedimentation stability; rheological properties; emulsion; порошок кореня селери; мікроструктура; седиментаційна стійкість; реологічні властивості; емульсія